MyndFood: a conversational agent for enhancing the cooking and eating experience - Parra, Mario O.; Favela, Jesus; Castro, Luis A. (Frontiers in Computer Science, 2025)
The integration of technology into cooking and eating routines often leads to distractions, hindering mindfulness. Mindful eating involves awareness of the present moment and attention to sensory experiences. While mindful eating has been promoted, mindful cooking remains underexplored. As conversational agents become increasingly popular in diverse fields like education, healthcare, and e-commerce, we are leveraging this technology to promote mindfulness practices that enhance the cooking and eating experience. This paper introduces MyndFood, a conversational agent designed to promote mindful cooking and eating. We describe the development process of MyndFood and present the outcomes from a user experiment involving 40 participants who engaged with the system while preparing sushi. The study employed a between-subjects design featuring two conditions for the agent: mindful and non-mindful. Results indicate that participants in the mindful condition experienced greater enjoyment and heightened food awareness compared to those in the non-mindful condition. These findings suggest that conversational agents can enhance hedonic experiences and improve food awareness by promoting mindful practices.